Exegese und Theologie: über Bedeutung und Funktion der Exegese in der Theologie - Theißen, Gerd (Nederlands theologisch tijdschrift, 2004)
Biblical studies have been relevant for other disciplines as long as they were embedded within comprehensive theological programs such as the emancipation from the church dogma in liberal theology, the opening of transcendence in kerygmatic theology, the search for an authentic life in existential theology and the ecumenical dialogue in the last decades. The challenge of our time is the dialogue both with a secular approach to religion and with other religions. Biblical studies may achieve a new vitality if exegesis develops a twofold reading of the Bible both within the church and within the secular society, and represents biblical identity in the interfaith dialogue.